Evaluation of the Genotoxicity of Aqueous Extracts of Ilex paraguariensis St. Hil. (Aquifoliaceae) Using the Allium Test - Bidau, Claudio Juan (2004)
Infusions and concoctions of Ilex paraguariensis are used as medicinal, nutritional and stimulant beverages in southern South America. Crop production is about 300,000 tons/year in Argentina, where the consumption rate reaches 5–9 kg/capita/year. In this study, we assessed the cytotoxicity of aqueous extracts of I. paraguariensis in the Allium test and Artemia salina microwell test. The extracts were prepared from commercial and “home processed” (laboratory) and were tested at concentrations of 5–40 g/l. Both extracts significantly decreased root growth and the mitotic index (MI). These effects were greater for the commercial material for which concentrations ≥10 g/l virtually abolished mitosis. The disturbance of mitotic behaviour was significant at 5–10 g/l of the “home-processed” product and included c-mitotic phenomena (over-condensed and disorganized metaphases, sticky metaphases, arrested anaphases, binucleated interphases) which could contribute to the increase in metaphase and anaphase indexes. None of the extracts were cytotoxic in the Artemia salina test. It is concluded that the Allium test is adequate for a preliminary screening of genotoxicity of medicinal plants and that genotoxic effects can be increased by the commercial manipulation of the raw product.